Effectiveness of Supervision of Virtual Office Taxpayer Based on Evaluation of Supporting Factors for Taxpayer Supervision - Baihaqi, Muhammad; Sari, Dahlia (E-Jurnal Akuntansi, 2025)
Effective supervision of virtual office taxpayers (WP VO) is essential to optimize tax revenue, given the growth in the number of WP VO and the potential revenue that this represents. This study aims to analyze the effectiveness of WP VO supervision based on the constraints encountered, using an evaluation of factors supporting taxpayer supervision. The study was conducted at the Jakarta Pancoran Tax Office, which has a significant number of WP VO. A case study approach was used, employing a mixed method with data collection through questionnaires and interviews. The results of the study indicate that, out of the five supporting factors analyzed, the main challenges in WP VO supervision lie in the taxpayer and regulatory factors. Regarding the taxpayer factor, many taxpayers are uncooperative and have invalid profile data. Meanwhile, regarding the regulatory factor, there are no specific policies governing VO taxpayers to support the implementation of supervision. With the supporting factors for supervision not yet fulfilled, the implementation of VO taxpayer supervision is hindered and has not been effective.